Acute heat illness in underground miners : the clinical state, haematology, biochemistry and risk factors. - Donoghue, Alan M. (Curtin University, 2000)
Objectives - To examine the incidence, clinical state, personal risk factors, haematology and biochemistry of heat exhaustion cases occurring at a deep underground metalliferous mine. To describe the underground and surface thermal conditions associated with the occurrence of heat exhaustion cases.Methods - A one-year prospective case-series of acute heat exhaustion cases was undertaken at a deep underground metalliferous mine in tropical and Australia. A case-control study of body mass index (BMI) and maximal oxygen uptake (VO(subscript)2max) in heat exhaustion was also undertaken. A history was obtained using a structured questionnaire. Pulse rate, blood pressure, tympanic temperature and urine specific gravity were measured before treatment. Venous blood was analysed for haematological and biochemical parameters, during the acute presentation and after recovery. BMI and VO(subscript)2max were measured after recovery and in a group of controls. Psychrometric wet bulb temperature, dry bulb temperature and air velocity were measured at the underground sites where heat exhaustion had occurred. Air cooling power and psychrometric wet bulb globe temperatures were derived. Surface 24-hour mean wet bulb and dry bulb temperatures were recorded. Surface 24-hour mean wet bulb globe temperatures were derived.Results - 106 cases were studied in the case series. The incidence of heat exhaustion during the year was 43.0 cases per million man-hours. In February it was 147 cases per million man-hours. The incidence rate ratio for mines operating below 1200m compared to those operating above 1200m was 3.17. Mean estimated fluid intake was 0.64 litres/hour (SD 0.29, Range 0.08-1.50).The following were raised on acute presentation compared to recovery (P value, % of acute cases above the normal clinical range): neutrophils (P<0.001, 36%), anion gap (P<0.001, 63%), urea (P<0.001, 21%), creatinine (P<0.001, 30%), glucose (P<0.001, 15%), serum osmolality (P=0.030, 71%), creatine kinase (P=0.002, 45%), aspartate transaminase (P<0.001, 14%), lactate dehydrogenase (P<0.001, 9.5%), and ferritin (P<0.001, 26%). The following were depressed on acute presentation compared to recovery (P value, % of acute cases below the normal clinical range): eosinophils (P=0.003, 3 8%) and bicarbonate (P=0.0 11, 32%). Urea and creatinine were significantly raised in miners with heat cramps compared to miners without this symptom (P<0.001), while there was no significant difference in sodium concentration (P=0.384).Mean psychrometric wet bulb temperature was 29.0 degrees celsius (SD 2.2, Range 21.0-34.0). Mean dry bulb temperature was 37.4 degrees celsius (SD 2.4, Range 31.0-43.0). Mean air velocity was 0.54 m/s (SD 0.57, Range 0.00-4.00). Mean air cooling power was 148 W/m(subscript)2 (SD 49, Range 33-290). Mean psychrometric wet bulb globe temperature was 31.5 degrees celsius (SD 2.0, Range 25.2-35.3). Few cases (<5%) occurred at a psychrometric wet bulb temperature <25.0'C, dry bulb temperature <33.8'C, air velocity >1.56 m/s, air cooling power >248 W/m(subscript)2, or psychrometric wet bulb globe temperature <28.5 degrees Celsius.The three surface temperature variables were significantly higher on those days on which heat exhaustion occurred compared to those days on which it did not occur (P<0.001). The relative risk of heat exhaustion on days when the surface 24-hour mean wet bulb globe temperature was in the range 26.0-28.0 degrees celsius was 4.82 (95% CI 2.12-10.96).65 cases of heat exhaustion and 119 controls were studied in the case-control study. Heat exhaustion cases had a significantly higher BMI than controls (P=0.006). The odds ratios increased with BMI. For a BMI of 32.00-36.99, compared to a BMI of less than 27.00 the odds ratio was 3.63 (95% confidence interval 1.42-9.36). V0(subscript)2max was not significantly lower in cases than controls. The odds ratios for heat exhaustion increased with decreasing VO(subscript)2max, but not significantly. The sample size provided 80% power of detecting an odds ratio of 2.5 or greater.Conclusion - Heat exhaustion in underground miners is associated with hypohydration, neutrophil leukocytosis, eosinopenia, metabolic acidosis, increased glucose and ferritin, and a mild rise in CK, AST and LD. Heat cramps are associated with hypohydration but not hyponatraemia. The incidence of heat exhaustion increases during summer and at depth. An increased fluid intake is required. Heat exhaustion would be unlikely to occur if ventilation and refrigeration achieved air cooling power >250W/m2 at all underground work sites. Surface temperature data could be used at this mine to warn miners about the risk of heat exhaustion. Deep underground miners should be advised to maintain a BMI of 24-27.